Strategi Pemberdayaan UMKM Melalui Penguatan Kelembagaan dan Menejemen Usaha Berbasis Ekonomi Hijau - Arif Budianto; Susi Rahayu; Halil Akhyar; Moh. Bahtiar; Hurnah; Alfina Taurida Alaydrus (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2025)
This community service program aimed to enhance the institutional capacity and business management of MSME actors in Keroya Village, Aikmel District, East Lombok Regency through a green economy-based approach. The main challenges faced by local MSMEs included weak organizational structure, lack of financial recordkeeping, limited marketing strategies, and the absence of environmentally friendly practices in business operations. The activities were carried out through lectures, technical training, and direct mentoring involving the East Lombok Office of Cooperatives and MSMEs and the community service team from the University of Mataram. Evaluation was conducted using pre-tests and post-tests, participatory observation, and in-depth interviews. The results showed an increase in participants' understanding of the importance of institutional strengthening, business planning, and green economic principles. Several MSMEs began implementing financial recordkeeping, defining organizational roles, and initiating eco-friendly practices such as waste management and the use of recycled packaging materials. In conclusion, this program contributed to improving the independence of MSMEs and sustainable village business governance. The program’s outcomes also offer a potential model for replication in other villages aiming to develop local economies based on sustainability principles.